Argovit: application prospects in treatment of livestock and poultry in central Mexico; 2nd International Symposium on Nanoscience and Nanomaterials SINN, Ensenada, Baja California, Mexico, March 4-8, 2012, CNyN-UNAM, "Welcome to the Bionanotechnology Group" - Nunez M. M.; Garcia J. C. L.; Pinos J. M. R.; Bogdanchikova N.; Burmistrov V.; Pestryakov A. N. Aleksey Nikolaevich (2013, 2013)
В фонде НТБ ТПУ отсутствует